Methods of Teaching Speaking in Foreign Language Lessons - Usmonovich, Ishonkulov Sherzod (International Journal on Integrated Education, 2023)
This article contains interesting information about teaching to speak a foreign language using dialogues and monologues and other interesting exercises. The opinions of famous pedagogues on this topic are also mentioned.